It's special and it's specific: understanding the early childhood education experiences and expectations of young Indigenous Australian children and their parents - Martin, K; Martin, Karen L. (My University, 2017)
Whilst early childhood education is regarded as important for young Indigenous Australians and it has been a feature of policy since the 1960s, it does not receive the same attention as compulsory schooling for Indigenous Australian students. A serious lack of large-scale research contributes to the devaluing of early childhood education for young Indigenous Australians by some stakeholders such as governments, academics and research, but not for the main stakeholders, namely young Indigenous Australian children and their parents. This paper aims to address this by drawing on large-scale qualitative and quantitative data from the Longitudinal Study of Indigenous Children. First, it will analyse data pertaining to the experiences of Indigenous Australian children to uncover what they believe to be special about their early childhood education. Second, it will analyse data pertaining to the specific choices made by their parents regarding their early childhood education. The paper concludes by discussing the role of research in strengthening areas within Indigenous Australian early childhood education and identifying areas where it is valued to the same level as compulsory schooling.
Keywords: Children -- Indigenous; Education and Training -- Early Childhood; Families -- Parents and Parenting; Children -- Early childhood; Learning, education and training; Families and relationships; Families; Children; Education and Training; Parents and Parenting; Early Childhood; Early childhood; Indigenous; Learning, education and training; Families and relationships